ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR TEPUNG KELAPA SULAWESI UTARA - Julentia M. V. Makatita; Ribka M. Kumaat; Juliana R. Mandei (AGRI-SOSIOEKONOMI, 2016)
The objective of this research is to analyze the influence of coconut production, the Rupiah exchange rate against the US $, and the export prices of desiccated coconut to the volume of exports of desiccated coconut North Sulawesi. This research was conducted in March-May 2016, with the location of Manado City, North Sulawesi. The data used in this research is secondary data obtained from related agencies such as the Department of Industry and Trade in North Sulawesi, Central Agency Statistics in North Sulawesi,Indonesia Bank, and Agricultural Departmentof North Sulawesi.Besides, there were interviews conducted on one of the companies which exportedthe desiccated coconut in North Sulawesi, namely PT. Dimembe Nyiur Agripro, to support the secondary data that has been obtained. The variables measured in this research are coconut production (Kg/year), the Rupiah exchange rate against the US$ (Rupiah), and desiccated coconut export price (US$/Kg). Thedata used istime series in the period of 2006 - 2015. Thedata analysis used is multiple linear regression. The result of this research shows that significantly in the time period of 2006-2015 the coconut production has positive influence on exports of desiccated coconut. The exchange rate shows a positive tendency and the export prices show that there was negative impact tendency,though both are not significant statistically to the exports of desiccated coconut in North Sulawesi.